Analysis of implementation of group strategies among pre-service English teachers. (1st January 2013) - Chien, Chin-Wen
This article aims to discuss the implementation of grouping strategies among pre-service elementary school English teachers in terms of theoretical concepts, strategies and feedback from teachers in Taiwan. These grouping strategies were used not only to group learners but also to help them review language and teaching concepts. The case study was conducted during a single semester, from February to June, 2012. The participants included 16 pre-service English teachers in a Multimedia in English Language Teaching class, part of a teacher education program in Taiwan. This study presents the following conclusions. First, 18 grouping strategies were employed across five categories. Second, the pre-service English teachers held positive attitudes toward these grouping strategies because these strategies made learning fun and creative. Moreover, they thought these strategies helped them review their English and their background knowledge about language learning and teaching.